Trajectory Specification Language for Air Traffic Control - Russell A. Paielli (Journal of Advanced Transportation)
Trajectory Specification is a method of specifying aircraft trajectories with tolerances such that the position at any given time in flight is constrained to a precisely defined bounding space. The bounding space is defined by tolerances relative to a reference trajectory that specifies position as a function of time. The tolerances are dynamic and are based on the aircraft navigation capabilities and the traffic situation. This paper proposes a standard Trajectory Specification Language (TSL) based on the Extensible Markup Language (XML) to represent these specifications and to communicate them by datalink. The language can be used to downlink trajectory requests from air to ground and to uplink trajectory assignments from ground to air. The XML format can be converted to binary for operational use, if necessary, using Efficient XML Interchange (EXI) or Abstract Syntax Notation (ASN.1).